2015
DOI: 10.1002/2015jc011018
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of phytoplankton primary productivity in the Arctic Ocean from satellite ocean color/in situ chlorophyll‐a based models

Abstract: We investigated 32 net primary productivity (NPP) models by assessing skills to reproduce integrated NPP in the Arctic Ocean. The models were provided with two sources each of surface chlorophyll‐ a concentration (chlorophyll), photosynthetically available radiation (PAR), sea surface temperature (SST), and mixed‐layer depth (MLD). The models were most sensitive to uncertainties in surface chlorophyll, generally performing better with in situ chlorophyll than with satellite‐derived value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 136 publications
3
71
0
2
Order By: Relevance
“…Accurately assessing sea ice associated NPP in models is of particular importance since it can represent a dominant portion of total (water plus sea ice) NPP in regions covered by sea ice for most of the year (e.g., Gosselin et al, 1997;Fernández-Méndez et al, 2015). In general, pan-Arctic models of NPP, which include sea ice contributions to NPP are very limited (e.g., Lee et al, 2015) highlighting the need for improved sea ice algae model parameterizations.…”
Section: Sea Ice Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurately assessing sea ice associated NPP in models is of particular importance since it can represent a dominant portion of total (water plus sea ice) NPP in regions covered by sea ice for most of the year (e.g., Gosselin et al, 1997;Fernández-Méndez et al, 2015). In general, pan-Arctic models of NPP, which include sea ice contributions to NPP are very limited (e.g., Lee et al, 2015) highlighting the need for improved sea ice algae model parameterizations.…”
Section: Sea Ice Classesmentioning
confidence: 99%
“…Large-scale estimates of sea ice algal chl a biomass and PP are limited to modeling studies as satellites are unable to observe the underside of sea ice. Lee et al (2015) demonstrated that pelagic phytoplankton PP models for the Arctic Ocean were highly sensitive to uncertainties in chlorophyll a (chl a) and performed best with in situ chl a data. In situ ice algal chl a estimates used in models, however, are typically based on a small number of ice core observations (e.g., Fernández-Méndez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although global estimates of marine primary production tend to converge on a number around 40-50 GT yr −1 , the accuracy and precision on regional scales of the estimation protocols remain relatively poor, partly as a result of an incomplete understanding of how the photosynthetic performance of marine phytoplankton varies in the global ocean (Carr et al, 2006;Lee et al, 2015). Photosynthesis-irradiance (P-E) parameters derived from carbon uptake experiments conducted over a controlled range of available-light levels provide a means of comparing the photosynthetic characteristics of marine phytoplankton across different natural populations and cultured isolates Prézelin et al, 1989;MacIntyre et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There are two main types of numerical models that have been applied to estimate NPP in the Arctic Ocean: satellite-based diagnostic models (reviewed in Babin et al [2015] and International Ocean Colour Coordinating Group (IOCCG) [2015], and assessed in Lee et al [2015]) and process-based coupled dynamic physicalbiological models run in either retrospective or predictive modes. This latter class of models has been applied to improve our understanding of the Arctic Ocean carbon sinks and sources using regional [e.g., Deal et al, 2011;Manizza et al, 2013;Slagstad et al, 2015;Zhang et al, 2010cZhang et al, ,2015 to global [e.g., Popova et al, 2010;Vancoppenolle et al, 2013] ice-ocean-atmosphere carbon cycle simulations.…”
Section: Introductionmentioning
confidence: 99%